2016
DOI: 10.1002/ccd.26456
|View full text |Cite
|
Sign up to set email alerts
|

Device‐in‐device: A transcatheter alternative to surgical explantation of a failing atrial septal defect intracardiac prosthesis

Abstract: A failing intracardiac device is traditionally addressed by open-heart surgery. Surgical explantation of the device, although a simple procedure, carries risks that some patients are not able or willing to cope with. Thus, a nonsurgical option seems desirable in selected cases. We report on four cases of early malfunction of the Polyvinyl Alcohol membrane of Ultrasept II™ CARDIA ASD devices. In all cases, transthoracic echo (TTE) surveillance 4-6 months after the index procedure, depicted significant left-to-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…5,6 However, It has been revealed that the CARDIA ASD prostheses show multiple PVA membrane perforations from 1 week to 24 months following postimplantation. [7][8][9][10][11][12] This malfunction was found independent from device size and noticed in the last two generations. The purpose of the study was to investigate retrospectively all ASD patients with CARDIA Ultrasept ASD occluder (an older version of the Ultrasept II) in our centre and examine whether spontaneous PVA membrane perforation developed in the long term.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…5,6 However, It has been revealed that the CARDIA ASD prostheses show multiple PVA membrane perforations from 1 week to 24 months following postimplantation. [7][8][9][10][11][12] This malfunction was found independent from device size and noticed in the last two generations. The purpose of the study was to investigate retrospectively all ASD patients with CARDIA Ultrasept ASD occluder (an older version of the Ultrasept II) in our centre and examine whether spontaneous PVA membrane perforation developed in the long term.…”
Section: Introductionmentioning
confidence: 76%
“…Covering the damaged membrane with a second device can be considered as an alternative to surgery. [8][9][10][11] The space between the nitinol struts made it possible to cross the long sheath for implanting the second device. Chamié et al applied 'device in device technique' to four patients and showed that implanting a second nitinol symmetrical double disk over the first one was technically feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported a total of four relatively early malfunctions of the polyvinyl alcohol membrane observed in a series of six consecutive patients treated with atrial septal defect Ultrasept II™ closure device from January to December 2014. Chamié et al 11 informed about four cases of early failure of the polyvinyl alcohol membrane and, in fact, they proposed a new and less invasive treatment for patients who present with early to mid-term failure of the polyvinyl alcohol sail-based devices. After 2015, Cardia Inc. developed a new version of this same device -Ultrasept II™in which a Goretex patch has been interposed between both discs.…”
Section: Discussionmentioning
confidence: 99%
“…Chamié et al [76] , 2016 -case series 4 4 out of 70 developed early fabric erosion, treated with device in device Nit Occlude ASD-R PFM Medical Mepro CE Mark Peirone et al [77] , 2014 -prospective observational 73 98.6% closure at 11 mo, no adverse events…”
Section: Asd Characteristics Amenable For Percutaneous Closurementioning
confidence: 99%